Day 2 Tue, September 27, 2016 2016
DOI: 10.2118/181324-ms
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the Envelope of Residual Oil Measurement: A Field Case Study of a New Class of Inter-Well Chemical Tracers

Abstract: The success of any improved oil recovery (IOR) project is largely dependent on how much oil is remaining to be mobilized within the targeted area of the partially depleted or mature reservoir. Partitioning tracers are generally used to measure residual oil saturation (Sor) or remaining oil saturation (ROS) in the near wellbore region via a single well chemical tracer test (SWCTT) or in an inter-well region via a partitioning inter-well tracer test (PITT). There is a limited repertoire of nonradioactive and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…One of our goals is to simulate field-scale tracer experiments (Sanni et al 2016). For this purpose, we generate a three-dimensional fractured geometry using seed points resulting in 2304 Voronoi blocks.…”
Section: First Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of our goals is to simulate field-scale tracer experiments (Sanni et al 2016). For this purpose, we generate a three-dimensional fractured geometry using seed points resulting in 2304 Voronoi blocks.…”
Section: First Resultsmentioning
confidence: 99%
“…Choice of a boundary condition (or rule) for a tracer crossing the interface between fracture and matrix is a non-trivial task: its inappropriate choice can significantly degrade accuracy of the 3D concentration field (Szymczak and Ladd, 2003). In our simulations we use specular reflection boundary condition, which is more difficult to program but it provides correct distribution of tracer concentration compared to alternative boundary conditions.…”
Section: Random-walk Particle-tracking Methodsmentioning
confidence: 99%
“…In our analysis, we strive to (a) perform simulations in the diffusion-dominated regime (Pe = 20) and (b) achieve realistic exit times for the distributions of tracers. For orientation, we consider the experimental field data from Sanni et al 5 The authors reported the distance of ∼610 m between tracer injection and detection (injector-producer distance). Their data suggest that the maxima of produced tracer concentrations are at ∼250, ∼350, and ∼450 days for the partitioning coefficients of K = 0, 2, and 4, respectively.…”
Section: Article Scitationorg/journal/phfmentioning
confidence: 99%
“…In tracer injection tests designed to estimate remaining oil saturation, it is common practice to use tracers with several partitioning coefficients K. 5,65 This is done to improve the reliability of the experimentally obtained values of S est o . As our results demonstrate, variation of K within a practical range (K ≈ 2, .…”
Section: Article Scitationorg/journal/phfmentioning
confidence: 99%
See 1 more Smart Citation